The Other side of airport crime : uncovering internal conspiracies (2013)
Shares some of the practices implemented at Schiphol Airport in the Netherlands to deal with internal conspiracies, that is, activity by corrupt airline / airport workers who abuse their rights of access at airports and conspire with criminal organisations to circumvent official control regimes on immigrants, prohibited / restricted commodities and large quantitites of revenue-generating goods; or facilitate the theft of high-value consignments.
Keywords: AIRCRAFT